Investigating the potential underdiagnosis of primary hyperparathyroidism at the University of Arkansas for Medical Sciences - Quilao, Raymond J. (Laryngoscope Investig Otolaryngol, 2020)
INTRODUCTION: Primary hyperparathyroidism (PHPT) is a condition in which one or more parathyroid glands secrete excess amounts of parathyroid hormone (PTH). In short, PHPT is characterized by hypercalcemia/hypercalciuria with concurrent elevated PTH levels. This condition is known to increase the risk of cardiovascular disease, osteoporosis, psychiatric disturbances, and renal complications. As of now, the disease typically runs a long course before being identified and treated. At present, surgery is the only viable treatment option for patients with this disease. Publications from other tertiary centers have identified a large‐scale underdiagnosis of PHPT. The aim of this study is to determine if similar trends exist at the University of Arkansas for Medical Sciences (UAMS). Moreover, this study was seen as a first step to developing a machine learning strategy to diagnose PHPT in large clinical data sets. METHODS: To evaluate for potential underdiagnosis of PHPT at UAMS, all patients from 2006 to 2018 with hypercalcemia and/or hypercalciuria (excluding those with known malignancies or other possible causes of excess serum calcium) were identified in electronic medical records. Then, it was evaluated whether these hypercalcemic/hypercalciuric patients received subsequent measurement of PTH levels necessary to confirm the diagnosis of HPT. RESULTS: At UAMS between 2006 and 2018, 28 831 patients were identified as having hypercalcemia and/or hypercalciuria. Of these patients, only 7984 ever had subsequent PTH levels tested. Therefore, 20 847 (72.3%) of these patients never had PTH labs drawn. CONCLUSIONS: These findings may represent a significant patient population in which PHPT remains undiagnosed due to lack of follow‐up. PHPT is often a silent disease with an insidious onset. At the point of diagnosis, typically the treatment is surgical removal of the offending parathyroid gland(s) (parathyroidectomy). Identification of underdiagnosis is the first step for subsequent improvement in the diagnosis of PHPT. Detection of this disease in its earlier stages may open the door for medical and lifestyle interventions, thereby decreasing long‐term sequelae of the disease, such as osteoporosis, myocardial infarction, or stroke.